Penerapan Media Kantong Pintar Panjang untuk Meningkatkan Kemampuan Matematika Dasar pada Siswa Kelas I SD Palm Kids Palembang - Miftahul Fitri Nur Afifah; Sri Anjani Virnalizi; Yeni Rahayu; Ditho Rizky Pratama; M. Hafiz Tolha Hasan (PT. Hasba Edukasi Mandiri, 2026)
This article describes the implementation of the Smart Length Pocket media to improve basic mathematics ability among first-grade students at SD Palm Kids Palembang. The study was written based on learning activities and classroom observations using a descriptive qualitative approach. The media was designed as a pocket containing picture cards, instruction cards, simple measurement cards, and concrete objects related to length. Students were invited to identify long and short objects, compare two objects, arrange objects from the shortest to the longest, and measure classroom objects using non-standard units such as hand spans, sticks, straws, paper clips, or other familiar materials. Data were collected through observation, learning documentation, simple interviews or informal question-and-answer sessions, and field notes during the learning process. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results show that the Smart Length Pocket media helped students become more involved in learning mathematics because the activities were concrete, playful, and close to their daily experiences. Students showed more courage to try, answer questions, discuss with friends, and use the media to explain their observations. The improvement was interpreted qualitatively, not through statistical testing, and appeared in students’ participation, understanding of long-short concepts, ability to compare and order objects by length, and initial skill in using non-standard measurement units. The media also helped the teacher and student teachers explain basic mathematical concepts in a simpler and more enjoyable way for young learners. The findings also support the use of simple classroom materials in early mathematics lessons.